Development of a module for identifying interests and self-potential for senior high school students - Rosyi, Ufti (Priviet Social Sciences Journal, 2025)
Based on interviews conducted by the researcher with tenth-grade students at a senior high school in Ponorogo Regency, it was found that the students were unfamiliar with the process of subject selection under the Merdeka Curriculum. This study aimed to develop a module that assists tenth-grade high school students in identifying their interests and self-potential to determine subject choices when entering the eleventh grade. This study employed a qualitative method and adopted research and development as its design. Data were collected through school-based interviews, which were then processed into descriptive explanations, producing categories that formed the basis of the module development. The assessment results revealed several categories, which were later organized into four chapters: the Merdeka Curriculum, identification of interests, self-potential, and a closing chapter. Based on these findings, the researcher compiled a module entitled “Me and How to Know Myself: A Module for Identifying Interests and Self-Potential to Guide Subject Selection for Senior High School Students” The dissemination results indicated that the module was positively evaluated regarding its design and content in addressing the needs of tenth-grade students. Therefore, it is recommended as a tool for high school classes to help students recognize their interests and self-potential in the context of subject selection when transitioning to Grade 11.